Pulmonary Macrophage and Dendritic Cell Responses to Cryptococcus neoformans - Nelson, Benjamin N.; Hawkins, Ashlee N.; Wozniak, Karen L. (Frontiers in Cellular and Infection Microbiology, 2020)
The fungal pathogen Cryptococcus neoformans can cause life-threatening infections in immune compromised individuals. This pathogen is typically acquired via inhalation, and enters the respiratory tract. Innate immune cells such as macrophages and dendritic cells (DCs) are the first host cells that encounter C. neoformans, and the interactions between Cryptococcus and innate immune cells play a critical role in the progression of disease. Cryptococcus possesses several virulence factors and evasion strategies to prevent its killing and destruction by pulmonary phagocytes, but these phagocytic cells can also contribute to anti-cryptococcal responses. This review will focus on the interactions between Cryptococcus and primary macrophages and dendritic cells (DCs), dealing specifically with the cryptococcal/pulmonary cell interface.